The past and current updates on diagnostic aspects of osteoarthritis - Tan, Wei Miao; Lau, Seng Fong; Md. Ajat, Mohd Mokrish; Mansor, Rozaihan; Megat Abdul Rani, Puteri Azaziah; Ng, Angela Min Hwei; Rahmad, Norasfaliza (Veterinary Association Malaysia, 2017)
Osteoarthritis (OA) is a progressive joint disease leading to the destruction of joint structures, which in turn causes severe and chronic pain to the patient. Since OA is a troubling and disruptive disease, numerous researches have been done into diagnosing this disease, both in the early and the late stages of the disease. Diagnostic modalities such as radiography, computed-tomography (CT), micro-computed tomography (μ-CT), and magnetic resonance imaging (MRI) have been used in OA research. Not only that, more advance measurements and criteria have been established to standardize OA research. Currently, the OA research has been delving into proteomic studies to search for potential disease biomarkers. Biomarkers such as urinary C-terminal telopeptide of collagen type 2 (uCTX-II) and cartilage oligometric protein (COMP) have shown potential to be both diagnostic and prognostic biomarkers. For this review paper, the developments in diagnostic modalities are discussed focusing more on proteomic and biomarker studies.